2020
DOI: 10.1111/jace.17025
|View full text |Cite
|
Sign up to set email alerts
|

SiOC modified carbon‐bonded carbon fiber composite with SiC nanowires enhanced interfibrous junctions

Abstract: Carbon‐bonded carbon fiber (CBCF) composites are promising lightweight and high efficient thermal insulators to be applied in aerospace area, but their practical applications are usually restricted by the low mechanical performance and poor oxidation resistance. To overcome these drawbacks, many efforts have been made in the fabrication of ceramic coated CBCF composites. However, the densities of these modified composites are usually very high, which would result in the reduction in their thermal insulation pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…First, the siloxane xerogel pyrolyzed and released SiO and CO gases . Then SiC nanowire nuclei were formed when SiO gas reacted with activated carbon sites (eq ) on the surface of SCFs. , Finally, the growth of nuclei into SiC nanowires was facilitated by the continuous supply and reaction of SiO and CO gases (eq ). As shown in Figures S2 and S3, the microscale pores constructed by SCFs provide the space for the growth of SiC nanowires.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the siloxane xerogel pyrolyzed and released SiO and CO gases . Then SiC nanowire nuclei were formed when SiO gas reacted with activated carbon sites (eq ) on the surface of SCFs. , Finally, the growth of nuclei into SiC nanowires was facilitated by the continuous supply and reaction of SiO and CO gases (eq ). As shown in Figures S2 and S3, the microscale pores constructed by SCFs provide the space for the growth of SiC nanowires.…”
Section: Resultsmentioning
confidence: 99%
“…32 Then SiC nanowire nuclei were formed when SiO gas reacted with activated carbon sites (eq 1) on the surface of SCFs. 5,33 Finally, the growth of nuclei into SiC nanowires was facilitated by the continuous supply and reaction of SiO and CO gases (eq 2). 34…”
Section: Resultsmentioning
confidence: 99%
“…fabricated in situ growth of 3D SiC nanowires reinforced SiOC/CBCF composite and found the mechanical performance of SiOC/CBCF composites could be dramatically enhanced originating from the pull‐out and bridging behavior of SiCnws. Recently, Su et al 22 . also reported the SiCnws could improve the interfibrous junctions in SiOC/CBCF composites via polymer impregnation pyrolysis (PIP) process.…”
Section: Introductionmentioning
confidence: 99%
“…Du et al 21 fabricated in situ growth of 3D SiC nanowires reinforced SiOC/CBCF composite and found the mechanical performance of SiOC/CBCF composites could be dramatically enhanced originating from the pull-out and bridging behavior of SiCnws. Recently, Su et al 22 also reported the SiCnws could improve the interfibrous junctions in SiOC/CBCF composites via polymer impregnation pyrolysis (PIP) process. However, to best of our knowledge, the in situ growth of SiC nanowires onto carbon fiber's surface to enhance the EMW absorption performance and the mechanical property of the SiOC ceramic matrix carbon fiber composites have been rarely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…SiC materials, including bulk SiC ceramic, SiC fiber, and SiC nanowires (NWs), are commonly used as structural and/or functional materials under extreme conditions due to their excellent mechanical strength, chemical inertness, and thermal stability 1–4 . Comparing with SiC bulk and fibers, SiC NWs exhibit unique properties, such as excellent flexibility and high tensile strength, and unique functions of one‐dimensional nanomaterials, 5–9 which brings them unique usage as strengthening and toughening reinforcements in ceramics, or as building blocks in deformable ceramic aerogels or electronic nanodevices 9–20 . For instance, the emerging SiC NW aerogels that are composed solely from SiC NWs usually exhibit ultralow density, ultralow thermal conductivity, and resilient compressibility.…”
Section: Introductionmentioning
confidence: 99%